The Effect of Using Read Cover Remember Retell (RCRR) Strategy Towards Students’ Reading Comprehension on Narrative Text in UPT SMP Negeri 1 Padang Gelugur - Nurhalimatussakdiah Nurhalimatussakdiah; Irwandi Irwandi; Syahrul Syahrul; Widya Syafitri (Pusdikra-Publishing.com, 2024)
This research was aimed at finding out the effect of using (RCRR) strategy towards student’s reading comprehension on narrative text at the ninth grade of UPT SMP Negri 1 Padang Gelugur. The rationality of this research was based on the students’ problems in reading comprehension. Firstly, the students’ achievements on reading comprehension narrative text was still low. Secondly, the strategy taken by the teacher in class was monotonous. Thirdly, the srtudents had difficulties on comprehending the detailed information on narrative text. This research employed quantitative method. In this research, the researcher used purposive sampling. The population of this research was the IX grade students at UPT SMP Negeri 1 Padang Gelugur. The research instrument of this research was reading test, which were tested for pre-test and post-test session. In this research, the researcher used descriptive and inferential statistic to analyzed the data. The result of the research indicated that was significant effect of using RCRR strategy towards students’ redading comprehension. It can be seen from p-value which was smaller than the alpha value(0,000<0,05). It is concluded that, using RCRR strategy gave significant effect towards students’ reading comprehension on narrative text.